PENGARUH MODE PEMBELAJARAN FLIPPED CLASSROOM BERBANTUAN MEDIA KOMIK TERHADAP HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 2 TAMAN NEGERI - Sinta Lisa Agustin; Arif Rahman Aththibby; Ade Gunawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low cognitive learning outcomes of science (IPA) in Grade IV students on abstract material such as photosynthesis due to the dominance of conventional learning modes and the lack of prior knowledge among students. This study aims to examine the effect and level of effectiveness of implementing the flipped classroom learning mode assisted by comic media on the IPA learning outcomes of Grade IV students at SD Negeri 2 Taman Negeri. The research method used is quasi-experimental design with a Nonequivalent Control Group Design. Samples were selected using purposive sampling, designating Class IVA as the experimental class (flipped classroom with comic media) and Class IVB as the control class (conventional). Data collection instruments used were objective multiple-choice tests (pre-test and post-test). Data analysis used the Independent Samples T-Test and N-Gain index assisted by SPSS. The results showed that: (1) There was a significant effect of implementing flipped classroom assisted by comic media on IPA learning outcomes, evidenced by a Sig. (2-tailed) value of 0.000 in the t-test; and (2) This learning mode was effective in improving academic achievement, indicated by a superior average N-Gain index of 77.57% (Very Effective category). This success was driven by optimal classroom time management, reduced boredom through comic visualization, and independent learning at home. The implication is that the integration of this mode and media becomes an innovative alternative to achieve active, student-centered science learning. Keywords: Flipped Classroom, Comic Media, IPA Learning Outcomes, Elementary School